1969
DOI: 10.1017/s0010417500005247
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation as an Explanatory Concept in Spanish History

Abstract: This essay can best be considered an anthropological venture in the field of recent and contemporary Spanish historiography. Our aim is twofold: an understanding of the nature of Spanish historical interpretation as it is elaborated by national historians; the examination of certain phases of intercultural contact critical in the formation of a distinct Spanish cultural form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

1974
1974
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…I also have no quarrel with their view that 'Research on growth and change should define a local region as the primary unit of analysis, in order to deal effectively with local structures which transcend community boundaries ' (1972: 330). In some of my own publications (Glick and Pi-Sunyer, 1969;Pi-Sunyer, 1970; I have stressed the importance of approaching Spain from a regional perspective, with respect both to the contemporary situation and also to its historical antecedents. Some years ago (Pi-Sunyer, 1967), I suggested that the regional approach would yield worthwhile results in the study of contemporary Mexican society, and not the least its social and economic dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…I also have no quarrel with their view that 'Research on growth and change should define a local region as the primary unit of analysis, in order to deal effectively with local structures which transcend community boundaries ' (1972: 330). In some of my own publications (Glick and Pi-Sunyer, 1969;Pi-Sunyer, 1970; I have stressed the importance of approaching Spain from a regional perspective, with respect both to the contemporary situation and also to its historical antecedents. Some years ago (Pi-Sunyer, 1967), I suggested that the regional approach would yield worthwhile results in the study of contemporary Mexican society, and not the least its social and economic dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Even before Franco's death, scholars inspired by Castro saw potential in the idea of convivencia once it had been freed from the constraints of such a complex, intramural debate on Spanish identity 7 . In a seminal article, ‘Acculturation as an Explanatory Concept in Spanish History’ (Glick & Pi‐Sunyer 1969), Thomas Glick and Oriol Pi‐Sunyer applauded Castro's determination to address cultural blending in medieval Spain, but lamented his lack of exposure to the anthropological theories that would have allowed him to identify the mechanisms of acculturation that actually made convivencia work. Siding with Castro in his assault on the ‘eternal Spain’ school represented by Sánchez‐Albornoz, they argued that cultures, far from being monolithic and static, are subject to constant reconfiguration, much of which is driven by their contact with and permeability to other cultures.…”
mentioning
confidence: 99%
“…Siding with Castro in his assault on the ‘eternal Spain’ school represented by Sánchez‐Albornoz, they argued that cultures, far from being monolithic and static, are subject to constant reconfiguration, much of which is driven by their contact with and permeability to other cultures. From their anthropological vantage point, Glick and Pi‐Sunyer saw Castro's convivencia as a form of ‘stabilized pluralism’, a ‘stage of arrested fusion or incomplete assimilation’ that was inherently unstable, ‘at best a modus vivendi , not an end of the values of either bloc’ (Glick & Pi‐Sunyer 1969, p. 153). Hence, the inevitability of the dramatic shift from the convivencia of medieval Spain to the ‘hostility, assimilation, and finally expulsion of the minority by the dominant culture’ that characterized late fifteenth‐ and sixteenth‐century Spain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In analyzing how the Canaries and the Indies were affected by a medieval notion of colonization, it is useful to rethink medieval history. Glick (1969) suggested that the Reconquista be analyzed as a process of acculturation. The value of his approach is the importance it places on adaptation to economic and social circumstances.…”
mentioning
confidence: 99%